Directional Goldstone waves in polariton condensates close to equilibrium - Dario Ballarini (Nature Portfolio, 2020)
Polariton condensates undergo continuous driving and dissipation, posing challenges for investigating their collective behaviour. Ballarini et al. adapt an oceanographic technique to measure the asymmetric occupation of the Goldstone mode and identify similarities with equilibrium condensates.